Taxes and the investment of mutual funds: Evidence from the German Investment Tax Reform - Reinald Koch; Lena Schön (Arbeitskreis Quantitative Steuerlehre (arqus), 2024)
This study investigates the impact of dividend taxes on equity mutual fund investments, using the 2018 German Investment Tax Reform as a unique case study. This reform eliminated the foreign tax credit for German fund investors, thereby introducing a new tax planning channel for German equity mutual funds. Analyzing data from 297 German equity mutual funds and comparable non-German equity and bond mutual funds, our findings indicate a significant shift in portfolio allocation post-reform. German equity mutual funds strategically shifted assets to countries with lower withholding tax rates and adjusted investments within countries to avoid taxes after the reform. We also examine the economic impact of the tax reform and find a negative relationship between the tax burden and fund inflows after the reform. Our findings provide valuable perspectives for policymakers, industry practitioners, and researchers by shedding light on the complex interplay between taxes, fund decisions, and investor responses.
Keywords: H26; G23; 330; Dividend Taxes; Mutual Funds; Investment Decisions; Tax Avoidance